2022
DOI: 10.1007/s10597-022-00970-6
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health among African American and Latinx Men who have sex with men after the COVID-19 Lockdown in Los Angeles – Findings from the HOPE cohort

Abstract: This study aimed to examine the depression and anxiety among men of color (primarily African American and Latinx) who have sex with men after the lockdown due to the COVID-19 pandemic. Outcomes included 21-item Beck Depression Inventory (BDI), 7-item Generalized Anxiety Disorder (GAD), and a 10-item COVID-related anxiety measure using a modified H1N1-related anxiety question. Independent variables were food insecurity and belief in government efficiency. Data were analyzed by Regression models with random clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Previous systematic reviews suggested that the prevalence of depressive symptoms among Chinese MSM was 30.0%–40.0%, which was higher than that of the general population in China (Fu et al., 2020 ; Lu et al., 2021 ; Wei et al., 2020 ). Additionally, evidence suggested that the outbreak of the coronavirus disease 2019 (COVID‐19) has also had a great impact on the mental health of MSM in the United States and France as the lockdown may separate them from sexual partners and reduce the acquisition of pre‐exposure prophylaxis (PrEP) (Di Ciaccio et al., 2022 ; Roux et al., 2022 ; Wang et al., 2022 ). Long‐term depressive symptoms could not only deteriorate MSM's psychological health but also increase the occurrence of unhealthy lifestyles, including high‐risk sexual behaviors, low adherence to PrEP, self‐harm, and even suicide intentions (Velloza et al., 2020 ; Vijayakumar et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous systematic reviews suggested that the prevalence of depressive symptoms among Chinese MSM was 30.0%–40.0%, which was higher than that of the general population in China (Fu et al., 2020 ; Lu et al., 2021 ; Wei et al., 2020 ). Additionally, evidence suggested that the outbreak of the coronavirus disease 2019 (COVID‐19) has also had a great impact on the mental health of MSM in the United States and France as the lockdown may separate them from sexual partners and reduce the acquisition of pre‐exposure prophylaxis (PrEP) (Di Ciaccio et al., 2022 ; Roux et al., 2022 ; Wang et al., 2022 ). Long‐term depressive symptoms could not only deteriorate MSM's psychological health but also increase the occurrence of unhealthy lifestyles, including high‐risk sexual behaviors, low adherence to PrEP, self‐harm, and even suicide intentions (Velloza et al., 2020 ; Vijayakumar et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%